Associations among interpretation bias, craving, and abstinence self-efficacy in adults with substance use disorders. (1st December 2019) - Beard, Courtney; Peckham, Andrew D.; Griffin, Margaret L.; Weiss, Roger D.; Taghian, Nadine; McHugh, R. Kathryn
Highlights: We examined interpretation bias in an inpatient SUD sample. Interpretation bias was correlated with anxiety and substance use symptoms. Interpretation bias predicted craving and situational confidence. Sex and substance type (opioid vs alcohol) did not moderate these relationships. Interpretation bias might be an important individual difference variable in SUDs. Abstract: Objective: Interpretation bias is a crucial therapeutic target in emotional disorders. However, few studies have examined the role of interpretation bias in substance use disorders (SUDs). Our specific aims were: (1) to examine whether interpretation bias was associated with craving and abstinence self-efficacy, and (2) explore potential moderators of these associations, including anxiety severity, sex, and substance type. Methods: Adults attending an inpatient SUD treatment program ( N  = 224; mean age = 38.95; 67% male/33% female; 68% primary alcohol use disorder/29% primary opioid use disorder) completed the Word-Sentence Association Paradigm (WSAP) with ambiguous situations related to general anxiety domains (e.g., daily stress, health, relationships), as well as measures of craving (Craving Scale), abstinence self-efficacy (Brief Situational Confidence Scale), and anxiety symptoms (Overall Anxiety Severity and Impairment Scale [OASIS] and Anxiety Sensitivity Index-3). Results: Negative interpretation bias was modestly associated with more craving ( r  = .23, p  =  .001) and less confidence to resist using substances ( r = -0.23, p  =  .001). In multiple linear regression models that included the anxiety measures, interpretation bias was the most robust predictor of craving and abstinence self-efficacy. Sex ( N  = 224) and substance type (opioid vs. alcohol; n  = 219) did not moderate these relationships. Conclusions: These findings suggest that interpretation bias might be an important individual difference within SUD populations.